2012
DOI: 10.3917/cdge.052.0197
|View full text |Cite
|
Sign up to set email alerts
|

La transversalité du genre : l'islam et les musulmans dans la presse suisse francophone

Abstract: Résumé Cet article a pour objectif d’analyser le rôle que tiennent les questions de genre dans le discours public de certains médias suisses francophones sur les musulmans et l’islam. Au fil de l’analyse quantitative et qualitative du corpus d’une recherche, on montre que les questions de genre traversent les thématiques abordées par le débat public à propos de la compatibilité ou de l’incompatibilité de la culture musulmane avec celle de la Suisse. Cela amène une interprétation des résultats du point de vue d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…At the national level, Helbling (2010) has analysed individual attitudes by showing how ethnic and national self-understandings among Swiss citizens have had a significant impact on the interaction between xenophobia and Islamophobia. Considering gendered Islamophobia, Parini et al (2012) have shown that in the Swiss French-language media, gender issues function as a means to consolidate the alleged incompatibly between Islam and Western culture. Dahinden et al (2014) have studied how young people in the French-speaking canton of Neuchâtel frame the assumption of 'non-egalitarian Muslims' by intertwining gender, ethnicity and religious elements to define the boundaries of citizenship.…”
Section: Literature Review and Methodologymentioning
confidence: 99%
“…At the national level, Helbling (2010) has analysed individual attitudes by showing how ethnic and national self-understandings among Swiss citizens have had a significant impact on the interaction between xenophobia and Islamophobia. Considering gendered Islamophobia, Parini et al (2012) have shown that in the Swiss French-language media, gender issues function as a means to consolidate the alleged incompatibly between Islam and Western culture. Dahinden et al (2014) have studied how young people in the French-speaking canton of Neuchâtel frame the assumption of 'non-egalitarian Muslims' by intertwining gender, ethnicity and religious elements to define the boundaries of citizenship.…”
Section: Literature Review and Methodologymentioning
confidence: 99%
“…B. Behloul 2007;Behloul 2009;Behloul 2011;Dahinden et al 2011;Parini et al 2012), für den hier untersuchten Zeitraum finden sich jedoch mit Ausnahme von Ettinger (2018) (Ettinger 2018, 13-15). Wie Ettinger (2018, 16) schreibt, findet sich dazu kaum eine «neutrale, auf Bewertungen verzichtende Berichterstattung».…”
Section: Massenmediale Debatten Zu Islam Und Musliminnen -Forschungssunclassified
“…These debates take varying forms and intensity, depending on the regulation of religion and the extent to which laicity is or is not applied in each canton, Switzerland being a federal State (Ossipow 2003). Scholars have also demonstrated how the "veil" is used in Swiss media as a symbol of radical Islamism, oppression of women (echoing a process of attribution of extraordinary sexism to the Other described by Roux et al 2007), or incompatibility with democratic values (Parini et al 2012).…”
Section: The Swiss Contextmentioning
confidence: 99%